Silk vista baby versus pipeline embolization device for unruptured distal anterior cerebral artery aneurysms: A multicenter propensity-weighted comparative study - Da Ros, Valerio; Clarençon, Frédéric; Dmytriw, Adam A.; Jabbour, Pascal; Psychogios, Marios; Sporns, Peter; Puri, Ajit S.; Hassan, Ameer E.; Algin, Oktay; Möhlenbruch, Markus A.; Bergui, Mauro; Goren, Oded; et al. (Elsevier, 2026)
Background
Flow diversion is effective for unruptured distal anterior cerebral artery (DACA) aneurysms, yet comparative data between the Silk Vista Baby (SVB) and Pipeline Embolization Device (PED) in this challenging territory remain scarce.
Methods
We conducted a retrospective multicenter study using the CRETA Registry, including consecutive patients with unruptured DACA aneurysms treated with SVB or PED. The primary endpoint was complete angiographic occlusion (O’Kelly-Marotta grade D). Secondary outcomes included procedural characteristics, clinical outcome (modified Rankin Scale), and complications. Overlap weighting was applied to account for non-randomized treatment allocation. Predictors of occlusion were explored using penalized logistic regression. A sensitivity analysis using a reduced five-variable model was performed to assess model robustness.
Results
137 patients were included (79 SVB, 58 PED). Within the PED group, devices included Pipeline Flex (n = 34), Pipeline Flex with Shield Technology (n = 14), and Pipeline Vantage with Shield Technology (n = 10). After overlap weighting, baseline characteristics were balanced; the effective sample size was 100.4. SVB procedures more often used a single device; PED frequently required multiple stents. Procedure duration was shorter with SVB. Complete occlusion was achieved in 69.6% (SVB) and 70.7% (PED) of aneurysms, with no significant difference in adjusted analysis (OR 1.32, 95% CI 0.59–2.96). Favorable clinical outcomes were observed in both groups, with acceptable and comparable complication rates. No variable, including device type, independently predicted complete occlusion, a finding confirmed in a reduced five-variable sensitivity analysis (aOR 1.04, 95% CI 0.47–2.31; p = 0.915).
Conclusions
SVB and PED demonstrated comparable angiographic efficacy and clinical safety for unruptured DACA aneurysms. Despite procedural differences, mid-term occlusion rates and outcomes were similar. Device selection in this distal territory may be guided primarily by anatomical considerations and operator preference rather than expectations of differential performance.